Sports Policy on The Scope of Educational Sports Development Patterns: An Analysis Study - Muhammad Gilang Ramadhan; Amung Ma'mun; Nuryadi Nuryadi; Tite Juliantine (JUARA : Jurnal Olahraga, 2023)
This study aims to analyze the realization of the policy of educational sports development patterns based on sports law. In accordance with the mandate of the sports law that sports education is an important part of nation-building in order to improve the quality of life and human welfare. This study uses a descriptive qualitative approach. This research was conducted in Bogor Regency with the consideration that it is the only region that has a concentration on the development of sports education. This is certainly expected to be a role model for other regions in the development of sports education. Then by conducting observations, documentation studies, and interviews as a tool for data collection. To analyze the data collected, we designed ten indicators based on the essence of sports law in the scope of educational sports. Then, the data is analyzed by referring to the analysis method of the realization of Korten's policy which views three dimensions. The first dimension is the compatibility between the program and the user. Second, the suitability between user groups and the capabilities of the implementing organization. Third, compatibility between user groups and implementing organizations. The results of this study found that the realization of the applied educational sports development pattern policy was close to conformity with what was stated in the sports law. Although, there are still some aspects that are not optimal in their implementation, which is caused by the absence of a good relationship between the three dimensions, namely policies (programs), implementing organizations, and user groups (society). Therefore, the government as the policy maker by collaborating with the community must immediately improve in realizing the pattern of developing educational sports in accordance with the mandate of the sports law.